Independent Women or Family Crisis? Re-reading Qur'an 4:32 to Rethink Women's Independence as a Foundation of Muslim Family Resilience - Yoga Saputra; Rezky Fadly Saputra (Presscience, 2026)
The growing phenomenon of women’s independence has significant implications for the resilience of Muslim families. However, its relationship with Islamic normative teachings is often insufficiently addressed. This study examines women’s independence through a Qur’anic perspective, particularly Qur'an 4:32, which affirms equal rights of men and women to the fruits of their labor. Using a qualitative literature-based approach, the research analyzes Qur’anic texts alongside contemporary scholarship on gender relations and family resilience. The findings show that women’s independence integrates socio-economic, psychological, and spiritual dimensions consistent with Islamic values of justice and responsibility. When practiced proportionally, it contributes to economic stability, better communication, and greater participation of women in family decision-making. A normative reading of Qur'an 4:32 indicates that women’s independence is not a threat to family structure but a collaborative mechanism that supports the realization of a harmonious family (sakinah, mawaddah, wa raḥmah). Grounded in the principles of Maqāṣid al-Sharī‘ah, women’s independence can serve as a strategic foundation for strengthening Muslim family resilience in the modern era.